THE PROFICIENCY OF THE THIRD SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM UNIVERSITAS RIAU IN COMPREHENDING READING SECTION OF TOEFL - Melda Dwi Vega; Eliwarti Eliwarti; Novitri Novitri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2022)
This descriptive quantitative research was designed to discover the proficiency of the third-semester students of the English study program FKIP Universitas Riau in comprehending the Reading Section of TOEFL. The population of this research was the third-semester students of the English study program FKIP Universitas Riau which consisted of 119 students. The sample was 119 students selected by using the total sampling technique. The instrument of the research was a TOEFL Reading Comprehension Section test which consists of 50 multiple-choice questions. The students’ scores in the TOEFL Reading Test were analyzed in selecting skills based on the blueprint of the test related to the reading syllabus that samples took on Reading Comprehension III class. From the data analysis, the average score is 37. The researcher found that the students’ reading proficiency can be categorized as poor in level. Using Contexts for Vocabulary reaches the highest score (58), while Scanning for details is the lowest score (43). The finding implied that the third-semester students of the English study program FKIP Universitas Riau should improve their proficiency in comprehending Reading Section of TOEFL to get a better score.